PENGARUH HARGA DAN CITA RASA TERHADAP MINAT BELI KONSUMEN PADA UMKM KULINER PASAR SUMBUL KABUPATEN DAIRI - Iani Sianturi; Nalom Siagian; Jonson Rajagukguk (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze and determine the influence of price and taste on consumer purchasing interest in culinary MSMEs at Sumbul Market, Dairi Regency. The background of this study is based on the growing culinary business and increasing competition among MSMEs, requiring business owners to understand the factors that influence consumer purchasing interest. Affordable prices and good food taste are two important factors often considered by consumers before making a purchase. Therefore, this study was conducted to determine the extent to which price and taste influence consumer purchasing interest in culinary products sold by MSMEs at Sumbul Market. The research method used in this study was a quantitative survey approach. The population in this study were all consumers who made purchases at culinary MSMEs at Sumbul Market, Dairi Regency. The sampling technique used was non-probability sampling with an accidental sampling method, namely consumers who happened to be encountered by the researcher during the research. The sample size used in this study was 100 respondents. Data collection was carried out by distributing questionnaires to consumers shopping at Sumbul Market. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and the coefficient of determination (R²) using SPSS version 25. The results showed that price has a positive and significant effect on consumer purchasing interest. This indicates that the more affordable and appropriate the price compared to the product quality, the higher consumer purchase intention. Taste also has a positive and significant effect on consumer purchasing interest, indicating that food with a delicious, appealing taste that suits consumers' preferences can increase consumer repurchase intentions. Furthermore, the simultaneous test results indicate that price and taste significantly influence consumer purchasing interest among culinary MSMEs in Sumbul Market, Dairi Regency. Therefore, it can be concluded that appropriate prices and good taste are important factors that MSMEs need to consider to increase consumer purchasing interest and maintain the sustainability of culinary businesses in Sumbul Market, Dairi Regency.